Hardness of a bleaching-shade resin composite polymerized with different light-curing sources Microdureza de uma resina composta para dentes clareados polimerizada com diferentes fontes de luz fotoativadora - Giovana Mongruel Gomes; Abraham Lincoln Calixto; Fabio André dos Santos; Osnara Maria Mongruel Gomes; Paulo Henrique Perlatti D'Alpino; João Carlos Gomes (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The microhardness of a bleaching-shade resin composite polymerized with different light-curing units was evaluated. Composite samples (3M ESPE Filtek Supreme) were applied to brass rings (2 mm in thickness, 5 mm in diameter). Three commercial LED lights were used to polymerize the specimens and the results were compared to those of a conventional halogen light. The light sources used in the present study were: Demetron Optilux 401 (QTH), 3M ESPE Elipar FreeLight (LED 1); Kerr L.E.Demetron I (LED 2), and ColtoluxLED lights (LED 3). The microhardness of the top and bottom surfaces was assessed with a digital Vickers hardness-measuring instrument, under load. At the bottom surface, no significant difference among the light sources was observed (two-way ANOVA). At the top surface, the QTH light source presented significantly higher hardness values compared to the values observed when LED 1 and LED 3 were used. There were no significant differences between the QTH and LED 2 light sources. Significantly higher hardness values were also found at the top surface when compared to the values observed at the bottom surface. The power density of the polymerization light sources seemed to be responsible for the observed resin composite hardness, not their irradiance. Avaliou-se a microdureza de uma resina composta para dentes clareados fotoativada com diferentes fontes de luz fotoativadora. Espécimes de resina composta (3M ESPE Filtek Supreme) foram aplicados a cilindros de latão (2 mm de espessura, 5 mm de diâmetro). Três fontes comerciais de luz LED foram utilizadas para polimerizar os espécimes e os resultados foram comparados aos obtidos utilizando-se uma fonte de luz halógena convencional. As fontes de luz utilizadas no presente estudo foram: Demetron Optilux 401 (QTH), 3M ESPE Elipar FreeLight (LED 1); Kerr L.E.Demetron I (LED 2), e ColtoluxLED lights (LED 3). A microdureza das superfícies topo e base foram avaliadas com um microdurômetro digital (Dureza Vickers), sob aplicação de carga. Na superfície base não se observou diferença significante entre as fontes de luz utilizadas (ANOVA, dois critérios). Na superfície topo, a fonte de luz QTH apresentou valores de dureza significantemente maiores quando comparado aos valores apresentados quando LED 1 e LED 3 foram utilizadas. Não houve diferença significante entre QTH e LED 2. Observou-se também diferença significante entre os valores das superfície topo, que foram significantemente superiores, e base. A densidade de potência das fontes de luz fotoativadoras mostrou ser responsável pela dureza da resina composta e não a irradiância.